Problem-Oriented Gamification: Enhancing Creative Thinking Through the Electrical Monster Invaders Game - Valencia Fidelia Soetra; Nadi Suprapto; Adrian Bagas Damarsha; Indri Maya Ariana; Khofifatur Risma Faradillah; Muhammad Ghiyats Naufal; Husni Mubarok; Alif Syaiful Adam (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
Physics education continues to face challenges due to students’ low levels of creative thinking skills (CTS) and the limited integration of problem-solving with gamification approaches in electromagnetic induction material. The research aims to describe significant differences in students’ CTS following problem-oriented gamification (POG) instruction supported by Electrical Monster Invaders (EMI), as well as students’ responses to the instruction. This research uses a quantitative experimental design involving one experimental class and two replication classes. Data collecting through CTS tests and student response questionnaires, analyzed using partial least squares structural equation models (PLS-SEM) to identify patterns of relationships among variables. The results indicate that POG-assisted learning using EMI effectively and consistently enhances CTS across all groups. Improvements were observed in every indicator. Structural analysis explains that POG plays a dominant role in shaping CTS, while the EMI serves as a supporting medium with an acceptable level of model fit. This study confirms that integration of problem-based learning, gamification, and interactive media is a relevant innovative strategy for enhancing CTS in physics learning (PL).